1997
DOI: 10.1046/j.1365-2168.1997.02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 200 restorative proctocolectomy operations: The John Radcliffe Hospital experience

Abstract: Continuous improvements in operative technique have simplified the procedure, and functional results, although variable, have generally been acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 13 publications
7
37
0
1
Order By: Relevance
“…Pouch-related complications occur in 35% with pelvic sepsis in 9.5% despite 80% diverting ileostomies. Recent studies (since 1995) have not shown an improvement [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Pouch-related complications occur in 35% with pelvic sepsis in 9.5% despite 80% diverting ileostomies. Recent studies (since 1995) have not shown an improvement [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported on outcome after colectomy among people with inflammatory bowel disease, [25][26][27][28][29][30] they are mainly small, short term studies in specialist departments, which have reported a relatively good prognosis. We used routinely collected data to investigate mortality after colectomy for inflammatory bowel disease in large population based settings.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative incidence of pouchitis varies from 20 to 50%, depending on the definition and length of follow up. [3][4][5][6][7][8] When followed for more than 10 years, approximately half experience pouchitis at least once. 7 Antibiotic therapy is often effective, but 5-15% of patients with an IPAA created for ulcerative colitis experience ''refractory or frequently recurrent'' pouchitis.…”
mentioning
confidence: 99%